2004
DOI: 10.1016/j.jasms.2004.08.010
|View full text |Cite
|
Sign up to set email alerts
|

A case study of de novo sequence analysis of N-sulfonated peptides by MALDI TOF/TOF mass spectrometry

Abstract: The simplicity and sensitivity of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry have increased its application in recent years. The most common method of "peptide mass fingerprint" analysis often does not provide robust identification. Additional sequence information, obtained by post-source decay or collision induced dissociation, provides additional constraints for database searches. However, de novo sequencing by mass spectrometry is not yet common practice, most likely becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 47 publications
2
57
0
Order By: Relevance
“…In this experiment, PEG being a large and heterogeneous molecule, MS sequencing information on Lys 19 is missing as a result of PEG attachments. As fragments for the modified side chains of proteins, such as phosphates, glycans, or disulfide bonds, are typically not observed in the spectra from ISD, ECD, and ETD, in contrast to CID [30], the truncation of the ion series at Lys 19 is in line with the prediction that a conjugation with a 20 kDa PEG would truncate the sequence readout at that particular position. It is believed that our observation resembles the case of disulfide bonds characterization or the study of proline containing sequences, where their presence is characterized by missing sequencing information due to the presence of cyclic moiety [32].…”
Section: Determination Of Pegylation Site Using Reisdsupporting
confidence: 54%
See 1 more Smart Citation
“…In this experiment, PEG being a large and heterogeneous molecule, MS sequencing information on Lys 19 is missing as a result of PEG attachments. As fragments for the modified side chains of proteins, such as phosphates, glycans, or disulfide bonds, are typically not observed in the spectra from ISD, ECD, and ETD, in contrast to CID [30], the truncation of the ion series at Lys 19 is in line with the prediction that a conjugation with a 20 kDa PEG would truncate the sequence readout at that particular position. It is believed that our observation resembles the case of disulfide bonds characterization or the study of proline containing sequences, where their presence is characterized by missing sequencing information due to the presence of cyclic moiety [32].…”
Section: Determination Of Pegylation Site Using Reisdsupporting
confidence: 54%
“…Due to its remarkable sensitivity, low sample consumption, ease of sample preparation, and high-throughput capability, MALDI-TOF MS has also been successfully used for the analysis of synthetic polymers [20 -23]. Further advancement has led to the development of MALDI-TOF/TOF MS [24 -26], which has been extensively used in proteomics applications for characterizing biomarkers and important post-translational modifications (PTMs) [27][28][29][30]. In addition, its reflector in-source decay (reISD) capability enabled the topdown analysis of intact proteins.…”
mentioning
confidence: 99%
“…It has been demonstrated that indirect evidence can add to the significance of an identification [20]. Therefore, the identifications were further validated by using information such as the cleavage specificity of trypsin and sequence information resulting from known preferential fragmentation patterns of sulfonated peptides [8].…”
Section: Database Searchesmentioning
confidence: 99%
“…Keough et al [6] demonstrated that the N-terminus can be derivatized by acylation with 2-sulfobenzoic acid cyclic anhydride or chlorosulfonylacetyl chloride. N-Terminal sulfonic acid derivatives were subsequently proposed for peptide sequencing by ESI-MS, MALDI-TOF MS [7], and MALDI-TOF/TOF MS [8]. The introduction of a sulfo group facilitates the MS/MS fragmentation of singly charged peptide ions by providing a second "mobile" proton which lowers amide bond strength and allows more facile unimolecular decay [9].…”
Section: Introductionmentioning
confidence: 99%
“…We did not succeed in registering ESI spectrum of this peptide due to low stability of its molecular ion. Figure 4 clearly indicates that sulfobenzoylation results in increasing of y-series ion intensities as expected [40,46]. Head-to-tail cyclization is suppressed.…”
Section: Sulfobenzoylation Of Phe 3 Leupro 2 -Nhmentioning
confidence: 62%